2023
DOI: 10.3390/cancers15153868
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Collagen I Differentially Regulates the Metabolic Plasticity of Pancreatic Ductal Adenocarcinoma Parenchymal Cell and Cancer Stem Cell

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a 5-year survival rate of less than 10 percent largely due to the intense fibrotic desmoplastic reaction, characterized by high levels of extracellular matrix (ECM) collagen I that constitutes a niche for a subset of cancer cells, the cancer stem cells (CSCs). Cancer cells undergo a complex metabolic adaptation characterized by changes in metabolic pathways and biosynthetic processes. The use of the 3D organotypic model in this study allowed us to manipulate the ECM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…As noted above, 2-deoxyglucose, the inhibitor of glycolysis, has shown beneficial effects in experiments with colon cancer [186], pancreatic cancer cells [307]. In another case, 2DG markedly increased DCA anti-cancer effects in Lewis lung carcinoma.…”
Section: Dca and 2d-deoxy Glucose (2dg)mentioning
confidence: 80%
See 1 more Smart Citation
“…As noted above, 2-deoxyglucose, the inhibitor of glycolysis, has shown beneficial effects in experiments with colon cancer [186], pancreatic cancer cells [307]. In another case, 2DG markedly increased DCA anti-cancer effects in Lewis lung carcinoma.…”
Section: Dca and 2d-deoxy Glucose (2dg)mentioning
confidence: 80%
“…In one, when different metabolic modifiers were tested against human pancreatic cancer xenografts in mice, the most effective regarding tumor growth inhibition was phenformin (5 out 12 individuals) and DCA (2 out of 6) [306]. DCA and other metabolic modifiers such as 2-deoxyglucose and phenformin increased cytotoxicity of paclitaxel albumin nanoparticles (nab paclitaxel) on pancreatic cancer cells [307]. Another study demonstrated that radioresistant PDAC cells over-expressed PDK and this resistance was reversed by DCA.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…In one, when different metabolic modifiers were tested against human pancreatic cancer xenografts in mice, the most effective at tumor growth inhibition were phenformin (5 of 12 individuals) and DCA (2 of 6) [ 306 ]. DCA and other metabolic modifiers, such as 2-deoxyglucose and phenformin, increased the cytotoxicity of paclitaxel albumin nanoparticles (nab paclitaxel) in pancreatic cancer cells [ 307 ]. Another study demonstrated that radioresistant PDAC cells overexpressed PDK and this resistance was reversed by DCA.…”
Section: Experimental Evidence For Dca Activity In Cancermentioning
confidence: 99%
“…As noted above, 2-deoxyglucose, the inhibitor of glycolysis, has shown beneficial effects in experiments with colon cancer [ 186 ] and pancreatic cancer cells [ 307 ]. In another case, 2DG markedly increased the anticancer effects of DCA on a Lewis lung carcinoma animal model.…”
Section: Dca and Some Interesting Associationsmentioning
confidence: 99%
“…Different studies using cancer cell lines demonstrated the responsibility of EMT in radio-or chemotherapy-driven resistance [81,92,93]. In fact, conventional anticancer drugs are mainly directed toward rapidly dividing cells, with EMT being associated with stem cell properties in cancer cells [94]. Furthermore, EMT can be involved in microenvironment modifications, causing the loss of cell-cell adherence and extracellular matrix remodeling, as well as in the interaction with the immune system, contributing to chemotherapy resistance [95][96][97].…”
Section: Mechanisms Of Cancers' Drug Resistancementioning
confidence: 99%